Effects of 2 different rehabilitation programs on jumping performance after ACL reconstruction: A randomized controlled trial - Jauregui Bidegain, Lucas; Izquierdo Redin, Mikel; Alfaro-Adrian, Jesus; Garcia-Arroyo, Jaime; Garcia-Tabar, Ibai; Sesma Mendaza, Andoni; Setuain Chourraut, Igor (Medicine (Baltimore), 2025)
Background: Objective criteria-based rehabilitation (OCBR) has shown potential in improving muscle strength and reducing knee laxity following anterior cruciate ligament reconstruction (ACLR). Limited evidence exists regarding its effectiveness in restoring functional jumping capacity. The objective of this study was to compare the effects of 2 rehabilitation programs on vertical and horizontal jumping performance at 3 to 6 and 12 months after ACLR. Methods: A longitudinal clinical double-blind randomized controlled trial was carried out. Forty recreational athletes (30 males, 10 females; age: 24 ± 6.9 years; height: 176.55 ± 6.6 cm; weight: 73.58 ± 12.3 kg), Tegner activity level of 7, were recruited. Participants were randomly assigned to either the OCBR or usual care rehabilitation (UCR) programs following primary ACLR. Vertical and horizontal jumping performance was assessed at 3-, 6-, and 12-month post-surgery. Results: OCBR group showed significantly better performance 6 months postoperatively among ACLR limbs in both vertical (unilateral drop jump 14.5 ± 3.6 vs 11.6 ± 4.6 cm, P < .05, ES = 0.7; bilateral drop jump 30.4 ± 6.4 vs 24.3 ± 6.0, P < .05, ES = 0.9) and horizontal jumping tasks (unilateral triple hop for distance 422.3 ± 52.3 vs 340.4 ± 53.1 cm, P < .05, ES = 1.5; unilateral cross over hop for distance 355.4 ± 52.0 vs309.7 ± 70.4 cm, P < .05, ES = 1.2). These differences remain consistent also at 12-months post-surgery compared to the UCR group between their operated limbs for vertical (unilateral drop jump 15.8 ± 3.2 vs 12.2 ± 3.3 cm, P < .05, ES = 1.1; bilateral drop jump 30.3 ± 4.9 vs 25.2 ± 6.5, P < .05, ES = 0.9) and horizontal maneuvers (unilateral triple hop for distance 452.1 ± 54.9 vs 385.0 51.9 cm, P < .05, ES = 1.6; unilateral cross over hop for distance 385.6 69.6 vs 285.1 60.3 70.4 cm, P < .05, ES = 1.5). Conclusion: The OCBR program led to superior functional performance outcomes at 6- and 12-months following ACL surgery, highlighting its potential as an effective rehabilitation strategy. Implementing an OCBR program post-ACL reconstruction improves functional performance in jumping tasks at 6 and 12 months compared with UCR rehabilitation.